Triumph - The Uninhabitable : Contemporary Danish and Hungarian Art. - Beke, László; Damgard-Sorensen, Henning; Dehlholm, Kirsten Tomas; Hegyi, Lóránd; Meyer, Peter S.; Néray, Katalin (Kobenhavn : Udstillingsbygningen ved Charlottenborg, 1990)
Abrahamsen, Leise Dich ; Bak, Imre ; Bang, Thomas ; Bukta, Imre ; Egemose, Claus ; Halasz, Károly ; Holten, Hans ; Ingemann, Paul ; Kiss, Péter ; Kovacs, Attila ; Krüger, Anders ; Lahoda, Thomas ; Landgreen, Malene ; Lavman, Maria ; Lugossy, Lászlo fe ; Moller, Mogens ; Ruge, Ane Mette ; Sass, Valéria ; Sugar, Janos ; Szilágyi, Lenke ; Szirtes, János ; Thejll, Mikael ; Trombitas, Tamás ; Vetö, János
biografie, filmografie, videografie
Engels & Deens & Hongaars
Triumph - The Uninhabitable : Contemporary Danish and Hungarian Art, Charlottenborg Exhibition Hall, Kobenhavn, April 28 - May 20, 1990 ; Mucsarnok Palace of Exhibition, Budapest, June 28 - July 22, 1990
boek
Keywords: Denemarken; Hongarije